Redemption - Wulff, Sabrina (Fieber Film, 2009)
Verzio FF Submission Out of suburban dreariness in Texas, Indiana and New York, out of lack of prospects or naïve admiration James, Dean and Dale were drawn into the military and sent to fight in Afghanistan and Iraq. The events over there shocked and sublimated them. They were trying to find legal ways out of the Air Force, the National Guard and Marines while they were home on leave – but without success. After agonizing for months they saw just one possibility: to turn their backs on their home country and flee across the Canadian border as thousands did before them during the Vietnam War. Traumatized, the three of them live together in Toronto, in a flat seen as a place of solidarity and comfort. However, their friendship shines though as the memories of war and the threat of deportation - increase. This film depicts their attempts to leave that life behind and begin another.